Метафізика пошуку в новелах Федора Потушняка - Лях, Т.Л. (Слово і Час, 2019)
Творчість Федора Потушняка формувалася під впливом сучасних йому культурно-історичних
реалій, європейської філософії. Розуміння прихованого, таємничого пронизує не лише лірику, а
й прозу письменника. У статті досліджено мотив пошуку крізь призму метафізичного в новелах
Ф. Потушняка – віднайдення персонажами втраченого зв'язку зі своїми духовними праосновами,
сенсу життя, творчості. Також розглянуто образи-символи, зміну часу і простору, інші художні
деталі. Fedir Potushniak’s works were closely connected to historical and cultural tendencies of literary
process of the late 19th – early 20th centuries and therefore refl ected Modernism in its European
and particular Ukrainian patterns, especially in its transcendental aspect concerning the metaphysical
nature of human being. Thus the literary works by Fedir Potushniak require a study that takes into
account philosophical ideas of his epoch.
Fedir Potushniak created his own philosophical conception considering human existence in
connection with its spiritual aspect. The writer’s attempt of uncovering the transcendental sense of
things is a peculiar feature of both his lyrics and prose. The paper interprets Potushniak’s short stories
in the light of his philosophical understanding of metaphysics. Philosophical and aesthetic approach
to the analysis of text involves using hermeneutical and aesthetic research methods.
Images, symbols, time and space variations and other literary details in the works by Fedir Potushniak
have been examined with regard to the metaphysical nature of human being and the motif of search
refl ecting the way of the characters to perceiving their own life and art. A special accent has been
made on the issue of human being in the writer’s short stories. The aim of search for magic things
such as buried treasure, fire, stone, flower, leads the characters to happiness, prompting them to
realize their own spiritual roots beyond time and space. Looking for their dream the characters of
Potushniak’s stories pass the inner way of spiritual formation. Interpretation of short stories by Fedir
Potushniak with regard to their philosophical background contributes to better understanding of the
writer’s creative phenomenon. The paper aims to reveal new meanings in Potushniak’s fiction and
outlines the aspects of interpreting it within interdisciplinary research.